The effects of mentoring on role stress, job attitude, and turnover intention in the hotel industry. (July 2015) - Kim, Samuel Seongseop; Im, Jaemoon; Hwang, Jinsoo
Abstract: In response to a dearth of mentoring studies in the hospitality literature, this study develops and tests a research model to investigate the influence of mentoring functions on role stress, job attitude, and turnover intention in the hotel industry. The data were collected from employees who had experienced mentoring programs at super-deluxe hotels in South Korea. This study conceptualized mentoring activity as having three main functions, including career development, psychosocial support, and role modeling. Structural equation model (SEM) analyses were used to explore the statistical significance of the paths between these functions and the main outcome variables. The psychosocial support function showed a significant relationship with all variables in the model (i.e., a positive effect on job satisfaction and organizational commitment, but a negative effect on role conflict, role ambiguity, and turnover intention). The relationships were not significant between the career development function and role ambiguity, between role modeling and role ambiguity, or between role ambiguity and turnover intention. The results will enable a better understanding of the effects of hotel mentoring programs and indicate directions for improving their outcomes. The findings can help hotel managers in developing more effective mentoring programs.